2019
DOI: 10.1371/journal.pone.0218504
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences and mortality risk in patients with heart failure and hyponatremia

Abstract: Background Hyponatremia is a well-established poor prognostic marker in patients with heart failure. Whether the mortality risk is comparable among different races of patients with heart failure and hyponatremia is unknown. Materials and methods Consecutive patients admitted with acute decompensated heart failure and an admission sodium level<135 mEq/L from 1/1/2001 through 12/31/10 were identified. Patients were divided into four groups based on self-reported race: whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For these purposes, several prognostic risk scores (PRSs) in patients with HF have been developed [10][11][12][13]. However, most of these scores have not been thoroughly externally validated and the effective values of predictors are differ among races and regions [14,15]. Moreover, current scoring systems paid less attention to outcomes in patients with ADHF during the vulnerable phase, and it is unclear whether they can be directly applied to ADHF patients.…”
Section: Introductionmentioning
confidence: 99%
“…For these purposes, several prognostic risk scores (PRSs) in patients with HF have been developed [10][11][12][13]. However, most of these scores have not been thoroughly externally validated and the effective values of predictors are differ among races and regions [14,15]. Moreover, current scoring systems paid less attention to outcomes in patients with ADHF during the vulnerable phase, and it is unclear whether they can be directly applied to ADHF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dysnatremia, including hyponatremia and hypernatremia, is very common in hospitalized patients ( 13 , 14 ) and complications of acute diseases, and results from interventions during patient treatment ( 15 , 16 ) or exists as a comorbid condition ( 17 ). Previous studies have shown that abnormal serum sodium concentrations are independent factors for poor prognosis of internal medicine patients ( 18 20 ) and patients with cardiac diseases ( 14 , 21 , 22 ). Studies show that patients with HF with AF frequently present with hyponatremia ( 23 , 24 ), which is associated with high mortality ( 25 ).…”
Section: Introductionmentioning
confidence: 99%